Endovascular anatomic reconstruction of the iliac bifurcation with covered stentgrafts in sandwich-technique for the treatment of complex aorto-iliac aneurysms. (1st November 2016) - Massmann, Alexander; Mosquera Arochena, Nilo Javier; Shayesteh-Kheslat, Roushanak; Buecker, Arno
Abstract: Objective: Endovascular anatomic reconstruction of iliac artery bifurcation in aorto-iliac aneurysms using commercial stentgrafts in sandwich-technique by bilateral transfemoral approach. Methods: 24 patients (mean 73.8 ± standard deviation 6.8 years) with complex aorto-iliac aneurysms (AAA): n = 17; diameter 64 ± 15 [48–100] mm; common-iliac-artery (CIA): n = 27; 43 ± 15 [30–87] mm; internal-iliac-artery (IIA): n = 14; 28 ± 8 [15–43] mm) were prospectively enrolled for EVAR with preservation of the IIA (n = 31; bi-lateral n = 7). Maintenance of antegrade flow to IIA by iliac reconstruction was performed in sandwich-technique prior to EVAR. Follow-up of 15.0 ± 10.8 [1–40] months included contrast-enhanced ultrasound and computed-tomography after 1 week, 3, 6 and every 12 months. Results: Initial technical success for anatomic reconstruction of the iliac arteries in 31 instances was 100%. Primary patency of iliac neo-bifurcations was 90.9% (20/22) at 6 months and 84.2% (16/19) at 1 year. Postprocedural gutter-endoleaks type 1b were obvious in 6.5% (2/31) of cases, which disappeared 3 months later. Aortic/iliac aneurysm-size after 1 year decreased (> 5 mm) in 61.5% of patients. No aneurysm-size increase or late rupture occurred. Conclusions: Endovascular reconstruction of the iliac bifurcation with commercial standard stentgrafts is safe and effective. Transfemoral approach allows extension of distal landing zone for EVAR while preserving the internal iliac artery blood-flow, even in unfavorable iliac anatomy.